Analisis Tingkat Keramahan Lingkungan Alat Tangkap Jaring Insang Dasar (Bottom Gillnet) Terhadap Penangkapan Ikan di Kab. Pangandaran - Syahna Dewi; Exist Saraswati (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2026)
This study aims to analyze the level of environmental friendliness of gillnet fishing gear operated by fishermen in Pangandaran Regency. Sustainable management of fishery resources is crucial in this region, given the high biodiversity and the pressure from environmentally damaging fishing activities. The methods used in this study include field observations, interviews, and the distribution of questionnaires to 30 respondents. Data analysis was conducted by scoring based on the nine criteria for environmentally friendly fishing gear established by the FAO Code of Conduct for Responsible Fisheries (CCRF) 1995. These nine criteria include gear selectivity, impact on habitat, fisherman safety, catch quality, consumer safety, impact on biodiversity, protection of endangered species, and social acceptance. The results showed that gillnet fishing gear in Pangandaran Regency obtained an average score of 28.3. Based on the CCRF assessment categories, this value places gillnets in the environmentally friendly category. Nevertheless, the selectivity aspect remains the lowest-scoring factor as the gear still catches more than three species with varying sizes. On the other hand, this fishing gear proved to be safe for habitats, poses no danger to fishermen, produces safe products for consumers, and is well-received socially by the local community.